Clinical and epidemiological characteristics of 320 deceased patients with COVID‐19 in an Italian Province: A retrospective observational study. Issue 11 (29th June 2020) - Biagi, Andrea; Rossi, Luca; Malagoli, Alessandro; Zanni, Alessia; Sticozzi, Concetta; Comastri, Greta; Gandolfi, Stefano; Villani, Giovanni Quinto
Abstract: Studies have described clinical features of patients with coronavirus disease (COVID‐19). However, limited data concerning the clinical characteristics of the Italian deaths are available. We aim to describe the clinical and epidemiological characteristics of 320 deceased from the Italian experience. We retrospectively collected all consecutive non‐survivor patients with laboratory‐confirmed COVID‐19 infection admitted to the Emergency Rooms (ERs) Piacenza Hospital Network during the first month of COVID‐19 pandemic in Italy. Clinical history, comorbidities, laboratory findings and treatment were recorded for each patient. A total of 1050 patients with confirmed COVID‐19 pneumonia were admitted to the ERs between 24 February and 22 March 2020. Three hundred and twenty (30.5%) patients died with a median age of 78.0 years, 205 (64%) non‐survivors were above 65 years old, 230 (71.9%) were male. Non‐survivor patients showed frequently several coexisting medical conditions, with hypertension being the most common comorbidity (235 patients, 73.4%). The in‐hospital mortality did not change during the progression of the pandemic. In this retrospective Italian study, most of COVID‐19 deceased patients were elderly male aged over than 65 years. Hypertension was the most common coexisting disease. In‐hospital mortality was high and showed no variation during the first month of the COVID‐19 italian epidemic. Highlights: This work highlights the clinical and epidemiological characteristics of COVID‐19 deceased patients in an Italian province with high in‐hospital mortality.